Molecular Signatures of Immunity and Immunogenicity in Infection and Vaccination - Haks, Mariëlle C.; Bottazzi, Barbara; Cecchinato, Valentina; De Gregorio, Corinne; Del Giudice, Giuseppe; Kaufmann, Stefan H. E.; Lanzavecchia, Antonio; Lewis, David J. M.; Maertzdorf, Jeroen; Mantovani, Alberto; Sallusto, Federica; Sironi, Marina; et al. (Frontiers in Immunology, 2017)
-